2015
DOI: 10.1155/2015/160189
|View full text |Cite
|
Sign up to set email alerts
|

Prescription of Chinese Herbal Medicine in Pattern-Based Traditional Chinese Medicine Treatment for Depression: A Systematic Review

Abstract: Traditional Chinese medicine (TCM) treatments are often prescribed based on individuals' pattern diagnoses. A systematic review of randomized controlled trials in Chinese and English literatures on TCM pattern-based treatment for depression has therefore been conducted. A total of 61 studies, 2504 subjects, and 27 TCM patterns were included. Due to the large variation of TCM pattern among participants, we only analyzed the top four commonly studied TCM patterns: liver qi depression, liver depression and spleen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 21 publications
0
35
0
1
Order By: Relevance
“…Nowadays, the first-line treatment for major depressive disorder is antidepressants including monoamine oxidase inhibitors, tricyclic antidepressants, and serotonin-norepinephrine and selective serotonin reuptake inhibitors (SN/SSRIs) [13, 30, 31]. Despite the wide variety of antidepressants available in the market, a significant proportion of patients cannot reach full remission or experience side effects [13, 32, 33].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Nowadays, the first-line treatment for major depressive disorder is antidepressants including monoamine oxidase inhibitors, tricyclic antidepressants, and serotonin-norepinephrine and selective serotonin reuptake inhibitors (SN/SSRIs) [13, 30, 31]. Despite the wide variety of antidepressants available in the market, a significant proportion of patients cannot reach full remission or experience side effects [13, 32, 33].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it has been reported that nearly 30% of the patients do not respond [8]. Side effects including nauseas, insomnia, agitation, weight gain, somnolence, sexual dysfunction, and cardiovascular adverse events have been reported [9, 31, 34]. Another downside of the use of antidepressants is the long treatment period needed to experience the beneficial antidepressant effect.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In line with this theory, researchers in China have proposed that acupuncture and moxibustion can improve the symptoms of depression by soothing the liver and regulating the mind [84]. Many herbal formulae have been used to treat depression, such as the Xiaoyao decoction and the Chaihu Shugan decoction [85]. The Chinese herb Radix Angelicae Sinensis is also considered to have antidepressant-like effects.…”
Section: Traditional Chinese Medicinementioning
confidence: 99%